Genetic differentiation of colombian populations of Anopheles darlingi Root (Diptera: Culicidae) (2017)
Anopheles darlingi Root is a primary vector of malaria in the neotropic region, a species not just highly anthropophilic but very efficient in transmitting Plasmodium species and considered the most important vector in the Amazon region. The main goal of this study was to determine the genetic structure of the A. darlingi populations using microsatellites (STR) in western and eastern regions of Colombia. DNA extraction was done with the cited protocol of band using the Genomic Prep™ cell and tissue isolation commercial kits. We used the STR reported by Conn et al (Mol Ecol Notes 1: 223-225, 2001). The analysis with STR proved there was a high genetic diversity and significant alterations of the Hardy-Weinberg equilibrium. The greatest genetic diversity was recorded in Mitu (Vaupes) (Na = 14, Ho = 0.520). The lowest was in Pueblo Nuevo (Cordoba) (Na = 12, Ho = 0.457). The eastern region and the Mitu (Vaupes) populations presented the highest number of primer alleles (Ap = 30; Ap = 13; Ap = 9), with variations between 0.010 and 0.097. The AMOVA revealed that the whole population underwent moderate genetic differentiation (F ST = 0.063, p < 0.05). The same differentiation was noticed (0.06 < F ST > 0.06, p < 0.05) with five of the six populations included in this job, and there was a low differentiation in the Las Margaritas (Santander) area (F ST = 0.02s3, p < 0.05). Our results suggest a slight positive correlation, which does not show a statistical significance between the geographic and genetic distances, probably suggesting that the moderate genetic differentiation found between pairs of populations does not need to be explained for the hypothesis of separation by distance.